2022
DOI: 10.3389/fcvm.2022.971321
|View full text |Cite
|
Sign up to set email alerts
|

Role of endothelial CXCR4 in the development of aortic valve stenosis

Abstract: BackgroundCXCL12/CXCR4 signaling is essential in cardiac development and repair, however, its contribution to aortic valve stenosis (AVS) remains unclear. In this study, we tested the role of endothelial CXCR4 on the development of AVS.Materials and methodsWe generated CXCR4 endothelial cell-specific knockout mice (EC CXCR4 KO) by crossing CXCR4fl/fl mice with Tie2-Cre mice to study the role of endothelial cell CXCR4 in AVS. CXCR4fl/fl mice were used as controls. Echocardiography was used to assess the aortic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…Interestingly, we observed that the eEPC lines expressed platelet-derived growth factor-B (PDGF-B), inhibitor of differentiation 1 (ID1), and C-X-C Motif Chemokine Receptor 4 (CXCR4), with comparable level to AEC lines (Supplementary Figure S3). It has been reported that PDGF-B, ID1, and CXCR4 play a role in stimulating vascular circulation [31], preserving vascular commitment via TGFβ inhibition [13], and regulating tissue regeneration as well as angiogenesis [32], respectively. These data suggest that the eEPC lines possess global gene expression profiles regulating a molecular network of endothelial cells.…”
Section: Eepc Lines Express Surface Proteins and Cellular Markers Of ...mentioning
confidence: 99%
“…Interestingly, we observed that the eEPC lines expressed platelet-derived growth factor-B (PDGF-B), inhibitor of differentiation 1 (ID1), and C-X-C Motif Chemokine Receptor 4 (CXCR4), with comparable level to AEC lines (Supplementary Figure S3). It has been reported that PDGF-B, ID1, and CXCR4 play a role in stimulating vascular circulation [31], preserving vascular commitment via TGFβ inhibition [13], and regulating tissue regeneration as well as angiogenesis [32], respectively. These data suggest that the eEPC lines possess global gene expression profiles regulating a molecular network of endothelial cells.…”
Section: Eepc Lines Express Surface Proteins and Cellular Markers Of ...mentioning
confidence: 99%
“…3). It has been reported that PDGF-B, ID1 and CXCR 4 play a role in stimulating vascular circulation [30], preserving vascular commitment via TGFβ inhibition [13] and regulating tissue regeneration as well as angiogenesis [31], respectively. These data suggested that the eEPC lines possess global gene expression profiles regulating molecular network of endothelial cells.…”
Section: Eepc Lines Express Surface Proteins and Cellular Markers Of ...mentioning
confidence: 99%